Polyphosphazenes as Adjuvants for Animal Vaccines and Other Medical Applications - Chand, Dylan J.; Magiri, Royford B.; Wilson, Heather L.; Mutwiri, George K. (Frontiers in Bioengineering and Biotechnology, 2021)
Polyphosphazenes are a class of experimental adjuvants that have shown great versatility as vaccine adjuvants in many animal species ranging from laboratory rodents to large animal species. Their adjuvant activity has shown promising results with numerous viral and bacterial antigens, as well as with crude and purified antigens. Vaccines adjuvanted with polyphosphazenes can be delivered via systemic and mucosal administration including respiratory, oral, rectal, and intravaginal routes. Polyphosphazenes can be used in combination with other adjuvants, further enhancing immune responses to antigens. The mechanisms of action of polyphosphazenes have not fully been defined, but several systematic studies have suggested that they act primarily by activating innate immunity. In the present review, we will highlight progress in the development of polyphosphazenes as adjuvants in animals and their other medical applications.